2009
DOI: 10.3844/ajessp.2009.197.208
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methylene Blue from Aqueous Solution onto a Low-Cost Natural Jordanian Tripoli

Abstract: Problem statement: It is well documented that lead is one of contaminants of industrial wastewaters and its pollution exists in the wastewater of many industries. As a result, recent research has focused on the development of cost effective alternatives using various natural sources and industrial wastes. In this setting, the use of low-cost agricultural materials, waste and residues for recovering heavy metals from contaminated industrial effluent has emerged as a potential alternative method to high cost ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 24 publications
5
73
0
Order By: Relevance
“…The comparison of the q m values is given in Table 6. Our adsorbent did perform fairly well than others that have been previously reported (Bulut and Aydin 2006;De Oliveria Brito et al 2010;ALzaydien 2009;Ncibi et al 2007;Bhattacharya and Sharma 2005;Ansori and Mosayebzadeh 2010;Caparkaya and Cavas 2008;) while it performed below other adsorbents reported by others (Elmorsi 2011;Ofomaja 2007;Salleh et al 2011;Kannan andSundaram 2001 andOlajire et al 2013). …”
Section: Adsorption Isothermsupporting
confidence: 51%
“…The comparison of the q m values is given in Table 6. Our adsorbent did perform fairly well than others that have been previously reported (Bulut and Aydin 2006;De Oliveria Brito et al 2010;ALzaydien 2009;Ncibi et al 2007;Bhattacharya and Sharma 2005;Ansori and Mosayebzadeh 2010;Caparkaya and Cavas 2008;) while it performed below other adsorbents reported by others (Elmorsi 2011;Ofomaja 2007;Salleh et al 2011;Kannan andSundaram 2001 andOlajire et al 2013). …”
Section: Adsorption Isothermsupporting
confidence: 51%
“…27 The Freundlich isotherm is the most widely used nonlinear sorption model and is given by Eqn. (7).…”
Section: C0mentioning
confidence: 99%
“…However, due to the high cost of activated carbon, adsorption using cheaper materials are preferable. Several studies have shown that numerous low cost materials like potato starch (Thakkar et al, 2006), kaolinite (Ghosh and Bhattacharyya, 2002), jordanian tripoli (Alzaydien, 2009) and activated carbon prepared from periwinkle shells (Bello et al, 2008) can be successfully applied for the removal of MB from aqueous solution. However, only few of them could be employed effectively to remove dyes from waste water streams.…”
Section: Introductionmentioning
confidence: 99%